Konsistensi Penerapan Metode Mawdu‘i dalam Skripsi Program Studi Ilmu Al-Qur’an dan Tafsir Tahun 2019-2021 - Azizy, Jauhar; Dasrizal; Sihabussalam (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2021)
Al-Farmāwī’s thematic interpretation scheme (mawḍū‘ī) has inspired the development of Qur’anic studies in Indonesian Islamic higher education. The State Islamic Universities (PTKIN) in Indonesia as an Islamic scholarship locomotive have a significant role in the development of the methodology of Qur’anic interpretation. This article analyzes the consistency of the application of thematic interpretation method in the final project of the Qur’an and Tafsir students. This article employs the content analysis method and uses the concepts of al-Farmāwī’s thematic interpretation as a theoretical framework. This study concludes that the majority of undergraduate theses are inconsistent in applying the al-Farmāwī’s thematic interpretation method. The inconsistency lies in the accuracy in the selection of keywords that are used as the basis for collecting and determining the verses of the Qur’an, the organization of the verses of the Qur’an that are not based on the order of revelation (tartīb al-nuzūlī), the lack of citation of the hadith, the failure synchronization between the problem and the conclusion.